ANALISIS FIGUR AMBU DALAM PROSESI MAPAG PANGANTÉN SUNDA - Nurzaini, Mayang Amalia (LP2M ISBI Bandung, 2023)
Mapag Pangantén is a bride and groom welcoming procession what be held at a Sundandese wedding party. The bride and the groom would welcomed with traditional music and dance performance. This procession appeared in the 1920s and continues to grow until now. The development includes various aspects, one of which is appeared of Ambu’s figure on Mapag Pangantén procession. Ambu is a Léngsér’s wife who have humorous character. But in reality, representation of Ambu’s figure often contradict with the concept of Sundanese culture and norms in society. This research was conducted using a qualitative descriptive method with observation techniques and literature study.